Factors predicting rehabilitation outcome in patients after unilateral transtibial amputation due to peripheral vascular disease - Majstorović Biljana; Pešta Mladen (Vojnosanitetski Pregled)
Background/Aim. The primary rehabilitation in the prosthetic phase after amputation of lower extremities is of great importance for the improvement of the activities of daily living (ADLs) of persons with amputation and their successful social reintegration. The aim of this study was to examine the influence of independent predictors (age, gender, duration of rehabilitation, time between the amputation and the mounting of the prosthesis) on the success of the primary rehabilitation in the prosthetic phase after amputation of lower extremities. Methods. This retrospective clinical study included patients who underwent the primary rehabilitation in the prosthetic phase at the Institute for Physical Medicine and Rehabilitation “Dr Miroslav Zotović“, Banja Luka, in 2015. A total of 75 patients with unilateral transtibial amputation were included. Etiologically, these transtibial amputations occurred as a consequence of vascular complications of diabetes mellitus or peripheral occlusive arterial disease. Evaluation of the success of rehabilitation was performed at the end of the primary rehabilitation in the prosthetic phase and 3 months after the end of the treatment by means of K-levels classification system and Locomotor Capabilities Index (LCI) scale. Depending on the distribution of data, univariate and multivariate multiple regression analysis, post hoc Mann-Whitney test, Spearman’s correlation coefficient and Wilcoxon test were used for statistical analysis. Statistical significance of the found differences was set at p < 0.05. Results. A total of 75 patients, 55 (73.33%) men and 20 (26.67%) women, were included in this clinical trial. Average age of all participants was 63.5 ± 9.06 years, 61.8 ± 9.34 years for males and 68.1 ± 6.4 for females (p < 0.01). Average duration of rehabilitation was 27.69 ± 7.39 days in men and 33.9 ± 6.89 days in women (p < 0.01). Male patients had better functional results compared to females obtained by all analysed outcome measures (p < 0.01). Younger patients achieved better results, with the degree of statistical significance ranging between p < 0.05 and p < 0.001. The time from the amputation to the mounting of prosthesis and the duration of rehabilitation had no influence on the rehabilitation outcome. Conclusion. The present study identified age and gender of patients as relevant independent predictors of the success of rehabilitation. Although it was initially expected, this clinical trial did not prove the importance of the time from the amputation to the start of the primary rehabilitation in the prosthetic phase. In the future research other independent predictive factors, such as comorbidities, first and foremost cardiovascular diseases, medication, laboratory parameters and mental status, should be taken into account.